(untitled) (Research, Society and Development, 2020)
COVID-19 was classified as pandemic. Dentistry is a profession at high-risk. Consequently, standard measures taken for protection purposes are no longer effective enough to stop the virus from spreading. Thus, the aim of the present study is to evaluate the knowledge of dentists who work in Londrina city about the pandemic based on the application of online questionnaires. Collected data were subjected to descriptive analysis. In total, 197 dental surgeons participated in the present study; 71 were men and 126 were women. Internet was the medium mostly used to obtain information (95.43%). Fever (96.95%) and cough (86.29%) were the most remembered symptoms. The personal protective equipment mostly used during the visits comprised procedural gloves (93.40%), face shields (92.89), disposable caps (86.29%) and N95 / PFF2 masks (79.69%). Mandatory mask using and availability of 70% alcohol (96.44%) were the main actions taken to minimize contamination in dental offices. With respect to assistance, 49.74% of dental surgeons performed 4-hand procedures with vacuum pump when they used high-speed pen, whereas 44.16% of them have reducing triple syringe using to avoid aerosols; 70% alcohol was the substance mostly used to clean the office (97.46%). Therefore, dental surgeons in Londrina County have adequate knowledge about COVID-19 symptoms, transmission route, incubation period, infection control and about control measures to be taken to minimize contamination and virus outspread in dental care environments, since these measures are necessary to help protecting these professional and their patients.